On switched control design of linear time-invariant systems with polytopic uncertainties - De Souza, Wallysonn A.; Teixeira, Marcelo C. M. [UNESP]; Santim, Máira P. A.; Cardim, Rodrigo [UNESP]; Assunção, Edvaldo [UNESP] (Hindawi, 2013)
This paper proposes a new switched control design method for some classes of linear time-invariant systems with polytopic uncertainties. This method uses a quadratic Lyapunov function to design the feedback controller gains based on linear matrix inequalities (LMIs). The controller gain is chosen by a switching law that returns the smallest value of the time derivative of the Lyapunov function. The proposed methodology offers less conservative alternative than the well-known controller for uncertain systems with only one state feedback gain. The control design of a magnetic levitator illustrates the procedure. © 2013 Wallysonn A. de Souza et al.
Keywords: Feedback controller; Linear matrix inequality (LMIs); Linear time invariant systems; Magnetic levitator; Polytopic uncertainties; Quadratic lyapunov function; State feedback gain; Switched control; Linear matrix inequalities; Lyapunov functions; Switching systems; Time varying control systems; Control